Boarding Model Education Concept to Improve the Quality of Pesantren Education - Sigit Raharja (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
The purpose of this study is to determine the picture of the implementation of dormitory pattern education to improve the quality of Islamic education at PPMI Assalaam Sukoharjo, supporting and inhibiting factors in the implementation of dormitory pattern education to improve the quality of Islamic education at PPMIA, the results of dormitory pattern education to improve the quality of Islamic education at PPMIA. Research paradigm: qualitative, types: field research, with approaches: historical, sociological, normative theological, pedagogical, psychological, and managerial. Data sources: primary and secondary. The research location is at PPMI Assalaam Sukoharjo. Data collection techniques with in-depth interviews, documentation, and observation. Data validity testing uses data triangulation based on a data source, technique, and time. The analysis used is data reduction, data presentation, and conclusions. The results of the study are The implementation of dormitory pattern education in Assalaam has been going well, the activity program is jam-dense with intensive mentoring, coaching and supervision, integrated and comprehensive. The supporting factors are human resources, infrastructure, good management and curriculum, as well as support from parents, the community, and related agencies. The inhibiting factor is the bad character of students and parents who do not understand boarding school. The results include cognitive, affective, and psychomotor aspects. The recommendations of education providers are committed and consistent to condition students to be able to adjust, feel comfortable and be able to learn well in boarding school, fulfilment and development of eight national education standards, and education management based on superior integrated quality management.